Metacognition and modality: Exploring gender disparity in the frequency of vocabulary learning strategies among university ESL students - Syahabuddin, Khairiah; Sa'i, Sa'i; Alfiatunnur, Alfiatunnur; Nashriyah, Nashriyah; Sriyanda, Ricky; Al-Darary, Tijan (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2025)
Vocabulary plays a crucial role in second language acquisition, and effective vocabulary learning strategies can significantly enhance language proficiency. However, while various strategies have been studied extensively, the influence of gender on vocabulary learning preferences remains insufficiently explored. This study addresses that gap by examining the types of vocabulary learning strategies used by male and female students in the English Language Education Department and analysing how these strategies are implemented in their learning processes. The purpose of this study, which employed a mixed-method approach using quantitative and qualitative techniques, is to identify the dominant strategies used by each gender and determine whether significant differences exist between male and female learners in their approach to vocabulary development. Thirty students (15 males and 15 females) participated by completing a vocabulary learning strategy questionnaire, followed by in-depth interviews with three male and three female students to gain richer insights into their practical strategy use. The results indicate that both male and female students predominantly use metacognitive strategies to build their vocabulary. Female students, however, consistently showed higher engagement across all five categories of strategies: metacognitive, determination, social, memory, and cognitive. Interview responses supported these findings and revealed that both genders commonly utilized strategies such as watching movies, reading, practicing speaking, and group discussions. Interestingly, only male students reported using vocabulary games as a learning tool. This study contributes to the field of second language learning by highlighting gender-based tendencies in strategy use, which can help educators design more inclusive and effective teaching approaches.